Pengaruh Produktivitas Terhadap Pemberian Upah Tenaga Kerja Kontainer di Pelabuhan Yos Sudarso Ambon (Tinjauan Hukum Islam) - Narci, Narci; Ishaq, Mahmud; Amin, Darwis (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims at the level of wages earned by container labor at Yos Sudarso Port Ambon and Islamic law's view of labor productivity against container labor wages. This type of research uses field research (Library Research). Data collection techniques used are using questionnaires, observations, and interviews. The data analysis technique used in this study is qualitative descriptive, namely inductive, deductive, and comparative analysis. Based on the results of data analysis, it is known that the level of wages obtained by container workers at Yos Sudarso Port Ambon is not fixed. The wages earned depend on the amount and type of goods unloaded from the container, as well as the amount of labor per unit group. The average wage obtained ranges from Rp. 15,000 to Rp. 80,000 if there are items to be unloaded. If the average income is taken with a large amount of Rp. 50,000, this means that the income has been comparable to the amount of UMP for the city of Ambon, namely with a UMP of Rp. 1,500,000. The determination of wages based on Islamic law is subjective, namely considering human aspects, so that the amount of wages obtained is not too calculated but sincerity, seriousness, responsibility, and work motivation are the top priorities in order to achieve the mercy and pleasure of Allah SWT